Coming to America [videorecording (DVD)] - Landis, John, 1950-; Murphy, Eddie, 1961-; Murphy, Eddie, 1961-; Hall, Arsenio; Jones, James Earl; Amos, John, 1939-; Sinclair, Madge; Headley, Shari, 1964- (I love the 80's, 2006)
An African prince who must find a bride ... and the mission leads him and his loyal friend to Queens, New York. In disguise as an impoverished immigrant, the pamered prince relishes the chance to test his mettle in the urban wilderness.